Saliva exposure reduces gingival keratinocyte growth on TiO2-coated titanium - Sini Riivari; Nagat Areid; Elisa Närvä; Jaana Willberg; Timo Närhi (Journal of Materials Science: Materials in Medicine)
Abstract Bioactive, nanoporous TiO2-coating has been shown to enhance cell attachment on titanium implant surface. The aim of this study was to evaluate, whether the saliva proteins affect the epithelial cell adhesion on TiO2-coated and non-coated titanium. Grade V titanium discs were polished. Half of the discs were provided with TiO2-coating produced in sol with polycondensation method. Half of the TiO2-coated and non-coated discs were treated with pasteurized saliva for 30 min. After saliva treatment, the total protein amounts on surfaces were measured. Next, the hydrophilicity of discs were measured with water contact angle measurements. Further, the gingival keratinocyte adhesion strength was measured after 2 and 6 h of cultivation using serial trypsinization. In addition, cell growth and proliferation were measured after 1, 3, and 7 days of cell culture. Finally, cell morphology, spreading and adhesion protein signals were detected with high resolution confocal microscopy. As a result, in sol coated TiO2-surface had significantly higher hydrophilicity when compared to non-coated titanium, meanwhile both non-coated and TiO2-coated surfaces with saliva treatment had a significant increase in hydrophilicity. Importantly, the amounts of adhered saliva proteins were equal between TiO2-coated and non-coated surfaces. Adhesion strength against enzymatic detachment was weakest on non-coated titanium after saliva exposure. Cell proliferation and cell spreading were highest on TiO2-coated titanium, but saliva exposure significantly decreased cell proliferation and spreading on TiO2-coated surface. To conclude, even though saliva exposure makes titanium surfaces more hydrophilic, it seems to neutralize the bioactive TiO2-coating and decrease cell attachment to TiO2-coated surface. Graphical Abstract